Subclinical cardiac dysfunction in cancer patients: A case report - Ruiz-Mori, Enrique (2020)
Cardiotoxicity is a relatively new clinical entity which, in the case of heart failure, is a marker of poor prognosis in cancer survivors who have received more frequent treatments with anthracyclines or trastuzumab. In these patients, detecting a cardiac dysfunction in the subclinical stage can reveal early myocardial involvement and avoid further damage to the heart. Technological advances in imaging, such as the global longitudinal strain, and the increase in troponin I enable the detection of this condition. This case report involves a 17-year-old female patient who was diagnosed with osteosarcoma in her left leg and received anthracyclines. In the cardiovascular evaluation, she was asymptomatic, and showed normal left ventricular function (60 %), decreased strain rate (-15 %) and elevated troponin I levels (115 ng/mL). Asymptomatic cardiac dysfunction was diagnosed and carvedilol 6.25 mg/day was prescribed. After 3 months of treatment, the strain rate (-20 %) and troponin I (19 ng/mL) levels returned to normal. This is an example of the usefulness of new cardiooncology units that allow cancer patients to be evaluated, diagnosed and treated early in order to avoid cardiotoxicity and the resulting mortality.